A Case of Chronic Granulomatous Pancreatitis - Ethan Angle; Frida Teran-Garza; Alex Paschke; Bradley Manning (Annals of Internal Medicine: Clinical Cases)
We present a 23-year-old woman with a 4-year history of an ambiguous, nonmalignant pancreatic head mass and recurrent nausea/vomiting, right upper quadrant abdominal pain, jaundice, oral feeding intolerance, chronic portal vein thrombosis, and pancytopenia. A multidisciplinary effort with extensive history-taking, laboratory work-up, and repeated endoscopic ultrasound with fine-needle aspiration narrowed her differential diagnosis—which included IgG4-related disease—into the seventh instance of chronic granulomatous pancreatitis secondary to histoplasmosis that has been reported in the literature to our knowledge. The patient remains symptom free on her year-long course of itraconazole, and her satisfactory outcome is an exemplification of the diagnostic and therapeutic power in specialty consultation by hospitalists.